Inequalities in Health Impact of Alternative Reimbursement Pathways for Nirsevimab in the United States. (15th August 2022) - Gomez, Gabriela B; Nelson, Christopher B; Rizzo, Christopher; Shepard, Donald S; Chaves, Sandra S
Abstract: The target populations and financing mechanisms for a new health technology may affect health inequalities in access and impact. We projected the distributional consequences of introducing nirsevimab for prevention of respiratory syncytial virus in a US birth cohort of infants through alternative reimbursement pathway scenarios. Using the RSV immunization impact model, we estimated that a vaccine-like reimbursement pathway would cover 32% more infants than a pharmaceutical pathway. The vaccine pathway would avert 30% more hospitalizations and 39% more emergency room visits overall, and 44% and 44%, respectively, in publicly insured infants. The vaccine pathway would benefit infants from poorer households.